Mitigation of Salinity Stress in Wheat Seedlings Due to the Application of Phytohormone-Rich Culture Filtrate Extract of Methylotrophic Actinobacterium Nocardioides sp. NIMMe6 - Meena, Kamlesh K.; Bitla, Utkarsh M.; Sorty, Ajay M.; Singh, Dhananjaya P.; Gupta, Vijai K.; Wakchaure, G. C.; Kumar, Satish (Frontiers in Microbiology, 2020)
Salinity stress is among the foremost limiting factors for crop productivity. Microorganism-based interventions for salinity stress mitigation in crop plants have gained significant attention. We report the impact of microbial inoculation of a halotolerant methylotrophic actinobacterium (Nocardioides sp. NIMMe6; LC140963) and its phytohormone-rich bacterial culture filterate extract (BCFE) on wheat seedlings grown under saline conditions. The bacterium showed PGPR activity in terms of its growth in N-limiting media, and siderophore and phytohormone (indole-3-acetic-acid and salicylic acid) production attributes. Microbial inoculation and priming with BCFE resulted in improved germination (92% in primed seeds at 10 dS m-1), growth, biochemical accumulation (total protein 42.01 and 28.75 mg g-1 in shoot and root tissues at 10 dS m-1 in BCFE primed seeds), the level of antioxidant enzymes (SOD, CAT, PO and APX), and antioxidant enzyme related gene expression (CAT, MnSOD, POD and APX) in the seedlings grown under high salinity stress. LC-MS based characterization revealed predominance of salicylate and indole-3-acetate (RT 4.978 min; m/z 138.1 and 6.177 min; 129.1) respectively in the BCFE. The bacterium produced high amount of IAA (45.6µgml-1 of culture filtrate) and was tolerant to 10% NaCl in the media. The study suggested that although microbial inoculation offers stress mitigation in plants, the phytohormone-rich BCFE from Nocardioides sp. NIMMe6 has potential implications for defence against salinity stress in wheat.